Mechanical and Dynamic Behavior of Fused Filament Fabrication 3D Printed Polyethylene Terephthalate Glycol Reinforced with Carbon Fibers. Issue 16 (2nd November 2018) - Mansour, M.; Tsongas, K.; Tzetzis, D.; Antoniadis, A.
ABSTRACT: The mechanical and dynamic behavior of FFF 3D printed polyethylene terephthalate glycol (PETG) and PETG reinforced with 20% carbon fibers is presented in this paper using several experimental tests. Compression tests, cyclic compression tests, nanoindentation, and modal tests were used as the assessment procedures. The results reveal that the addition of carbon fibers decrease as much as 66% the compressive strain, while increase the modulus and the hardness by around 30 and 27%, respectively. The loss factor and damping as calculated from the cyclic compression and models tests dropped from 17.3 to 15.4% and 13.8 to 12.3%, respectively. GRAPHICAL ABSTRACT: